2021
DOI: 10.1530/eje-20-1147
|View full text |Cite
|
Sign up to set email alerts
|

Steroid reference intervals in women: influence of menopause, age and metabolism

Abstract: Objective. To investigate the impact of age, obesity and metabolic parameters on thirteen circulating steroids in reproductive and menopausal age. To define reference intervals (RI). Design. Cross-sectional. Methods. 325 drug-free, healthy and eumenorrheic women were selected from the general population. Independent relationships of LC-MS/MS-determined steroid levels with age, body mass index (BMI) and metabolic parameters were estimated. Reference sub-cohorts were defined for calculating upper and lower li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Studies in humans have demonstrated a circadian pattern of DHEA secretions in young subjects, which tend to disappear with aging (32,33). Notably, in humans, serum and salivary DHEA showed an elevated degree of correlation, and an elevated decline in salivary DHEA can be observed between 8 and 12 a.m. (33). Patterns of salivary DHEA concentrations at T0 observed in this study support the hypothesis of a daily rhythmicity of DHEA secretion also in the bovine.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Studies in humans have demonstrated a circadian pattern of DHEA secretions in young subjects, which tend to disappear with aging (32,33). Notably, in humans, serum and salivary DHEA showed an elevated degree of correlation, and an elevated decline in salivary DHEA can be observed between 8 and 12 a.m. (33). Patterns of salivary DHEA concentrations at T0 observed in this study support the hypothesis of a daily rhythmicity of DHEA secretion also in the bovine.…”
Section: Discussionsupporting
confidence: 79%
“…The distribution of the rough data observed at T0 for salivary HC in this study agrees with the circadian secretory patterns observed in bulls and, on average, they were higher in samples collected before 11:00 h. We are not aware of studies that investigated the circadian secretion of DHEA in cattle. Studies in humans have demonstrated a circadian pattern of DHEA secretions in young subjects, which tend to disappear with aging (32,33). Notably, in humans, serum and salivary DHEA showed an elevated degree of correlation, and an elevated decline in salivary DHEA can be observed between 8 and 12 a.m. (33).…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to explore whether the decrease of 3, 5-tetradecadiencarnitine in the bladder under estrogen deprivation is mediated by changes in fatty acid transport and mitochondrial energy metabolism. Although there is no unified conclusion on the effects of menopause on the levels and rhythms of cortisol (33)(34)(35), this study is the first to discover that estrogen deprivation can lead to a decrease in the cortisol concentration of bladder tissue. Recent studies have found that plasma cortisol is involved in regulating the day-night micturition rhythm of the bladder (36).…”
Section: Discussionmentioning
confidence: 76%
“…Further research is needed to explore whether the decrease of 3, 5-tetradecadiencarnitine in the bladder under estrogen deprivation is mediated by changes in fatty acid transport and mitochondrial energy metabolism. Although there is no unified conclusion on the effects of menopause on the levels and rhythms of cortisol [33][34][35], this study is the first to discover that estrogen deprivation can lead to a decrease in the cortisol concentration of bladder tissue. Recent studies have found that plasma cortisol is involved in regulating the day-night micturition rhythm of the bladder [36].…”
Section: Discussionmentioning
confidence: 76%